CONSUMER VIEW ON THE AXIS OF DIDEROT EFFECT AND UNPLANNED PURCHASE - Sabiha Kılıç; Kübra Müge Çakaröz; Funda Civek (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
People's shopping habits are changing day by day.Consumers' point of view towards the product has turned into an emotional quality rather than a material quality.Emotional consumers pay attention that their products are compatible with each other.This situation triggers the Diderot Effect in consumers.With this feeling,the consumer displays a continuous buying behavior.It directs the consumer,acting with the domino effect logic,to unplanned purchases.When consumers buy an initial product,they start to think that they also need other products with the logic of induction.In order to finalize this situation, they tend to buy complementary products.This instinctive desire for integrity is described as the Diderot Effect.The aim of the study is to examine the Diderot Impact Levels and Unplanned Buying trends of the consumers.The research data were obtained through a survey applied on social media.In the analysis of the data, descriptive statistics, percentage and frequency,ANOVA and Chi-Square analysis were used.The reliability of the scales used in the study was tested with the Cronbach Alpha method, and the scales were found to be "High Reliability".As a result of the analysis,it was determined that there was a relationship between the unplanned purchasing behavior of the consumers and the Diderot effect levels and that the consumers purchased other products that were complementary to the products they purchased, therefore they were under the influence of diderot.